Lineage tracing of T cell differentiation from T-iPSC by 2D feeder-free culture and 3D organoid culture - Ishiguro, Yoshitaka; Iriguchi, Shoichi; Asano, Shinya; Shinohara, Tokuyuki; Shiina, Sara; Arima, Suguru; Kassai, Yoshiaki; Sakai, Yoshiharu; Obama, Kazutaka; Kaneko, Shin (Frontiers in Immunology, 2023)
T cells induced from induced pluripotent stem cells (iPSCs) derived from antigen-specific T cells (T-iPS-T cells) are an attractive tool for T cell immunotherapy. The induction of cytotoxic T-iPS-T cells is well established in feeder-free condition for the aim of off-the-shelf production; however, the induction of helper T-iPS-T cells remains challenging. In this study, we analyzed T-iPS-T cells matured in 3D organoid culture at different steps in the culture process at the single-cell level. T-iPS-T cell datasets were merged with an available human thymocyte dataset based on single-cell RNA sequencing (scRNA-seq). Particularly, we searched for genes crucial for generating CD4 + T-iPS-T cells by comparing T-iPS-T cells established in 2D feeder-free or 3D organoid culture. The scRNAseq data indicated that T-iPS-T cells are similar to T cells transitioning to human thymocytes, with SELENOW, GIMAP4, 7, SATB1, SALMF1, IL7R, SYTL2, S100A11, STAT1, IFITM1, LZTFL1 and SOX4 identified as candidate genes for the 2D feeder-free induction of CD4 + T-iPS-T cells. This 2 This is a provisional file, not the final typeset article study provides single cell transcriptome data sets of iPS-T cells and leads to further analysis for CD4 + T cell generation from T-iPSCs.